MANAGERIAL PROCESS OF INTERACTION OF THE STRUCTURES OF PUBLIC AUTHORITY AND CIVIL SOCIETY - M. Yakovleva (Вестник университета)
The article deals with the interaction of civil society with the structures of public authority as a managerial process. The main forms of influence in administrative and political governance in the Russian Federation are investigated and, on the basis of this, the forms of public authorities' influence on civil society are determined within the management process. Basic concepts and models of interaction between public authorities and civil society are presented. It was revealed that there is interaction between civil society and the structures of public authority, as well as mutual management of both structures.